The Effect of Training, Career Development, and Role Clarity on the Performance of Employees at the Bogor Medium Tax Office - Akmal, Shofianto; Purwanto, Purwanto; Rahayu, Sri (Neo Journal of economy and social humanities, 2026)
This study examined the effects of training, career development, and role clarity on employee performance at the Bogor Medium Tax Office (KPP Madya Bogor). The research employed a quantitative causal research design to analyze the relationships among the variables. The population consisted of all 118 employees of KPP Madya Bogor, and a census sampling technique was applied, resulting in 118 respondents. Data were collected using a structured questionnaire measured with a five-point Likert scale. The data analysis techniques included validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis using SPSS version 20. The results showed that all measurement instruments were valid and reliable, and the regression model met the classical assumption requirements. The multiple linear regression analysis revealed that training, career development, and role clarity each had a positive and statistically significant effect on employee performance. Among the three variables, training demonstrated the strongest influence on employee performance, followed by role clarity and career development. The coefficient of determination indicated that a substantial proportion of the variance in employee performance could be explained by the combined effects of the three independent variables. These findings suggest that employee performance in public sector tax institutions can be enhanced through effective training programs, structured career development systems, and clear role definitions. The study provides empirical evidence for the importance of integrated human resource management practices in improving performance within government organizations, particularly in the context of tax administration.